A IoT-Based Fire Safety Detection and Suppression Control System - Mohamad, Nursalwa Farahani; Khalid Isa (Evolution in Electrical and Electronic Engineering, 2024)
It is important to identify fires in homes to avoid property loss due to both natural and caused fires. Fire detection will be crucial because every life lost is very meaningful. Fires can occur anywhere and anytime but having a fire detection and suppression control system helps keep the family safe. Some people are unaware of the need for a fire detection and suppression control system. They believe they will smell the burning and run out of time. According to the study, the average time it takes for a building to burn down is only 60 seconds. So, by the time they smell the fire and decide to run to save themselves, the house has most likely been destroyed by the fire. The Internet of Things (IoT) is a network of computers that are both wired and connected to the Internet. This equipment can be linked over the Internet, allowing users to alter or gather data from it. This project used a wide range of sensors to detect the existence of flammable gas, the existence of fire and warn the user. In addition, a preventive approach is frequently used by installing a solenoid valve and a water sprinkler on it that can stop the gas leak when MQ-7 detects the presence of gas and also sprays water when the IR flame sensor detects a fire. The IoT-Based Fire Safety Detection and Suppression Control System plays an important role in helping people take proper precautions and manage the situation when fires happen by getting alerts through their devices.